Clues to the Etiology of Bile Duct Injury in Biliary Atresia - Mack, Cara L.; Feldman, Amy G.; Sokol, Ronald J. (Seminars in Liver Disease, 2012)
Biliary atresia (BA) is an infantile obstructive cholangiopathy of unknown etiology with suboptimal therapy, which is responsible for 40 to 50% of all pediatric liver transplants. Although the etiology of bile duct injury in BA in unknown, it is postulated that a pre- or perinatal viral infection initiates cholangiocyte apoptosis and release of antigens that trigger a Th1 immune response that leads to further bile duct injury, inflammation, and obstructive fibrosis. Humoral immunity and activation of the innate immune system may also play key roles in this process. Moreover, recent investigations from the murine BA model and human data suggest that regulatory T cells and genetic susceptibility factors may orchestrate autoimmune mechanisms. What controls the coordination of these events, why the disease only occurs in the first few months of life, and why a minority of infants with perinatal viral infections develop BA are remaining questions to be answered.
Keywords: neonatal cholestasis; adaptive immunity; innate immunity; humoral immunity